2002
DOI: 10.1182/blood.v99.1.36
|View full text |Cite
|
Sign up to set email alerts
|

The hypercoagulable state in thalassemia

Abstract: Thalassemia is a congenital hemolytic disorder caused by a partial or complete deficiency of ␣-or ␤-globin chain synthesis. Homozygous carriers of ␤-globin gene defects suffer from severe anemia and other serious complications from early childhood. The disease is treated by chronic blood transfusion. However, this can cause severe iron overload resulting in progressive organ failure. Some forms of ␣ thalassemia are also associated with a similar clinical picture. Despite the difficulties associated with treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
391
2
11

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 440 publications
(415 citation statements)
references
References 81 publications
11
391
2
11
Order By: Relevance
“…The target organs for thrombosis and infarction found in this model, however, are similar to those observed in human disorders characterized by hemolysis and thrombosis, such as thalassemia and sickle cell disease (Smith, 1996;Eldor and Rachmilewitz, 2002;Ezov et al, 2002;Shabat et al, 2004). Furthermore, enhanced red blood cell and endothelial cell interaction has been demonstrated both in this animal model and human thrombotic diseases Yedgar et al, 1999;Koshkaryev et al, 2003).…”
supporting
confidence: 76%
“…The target organs for thrombosis and infarction found in this model, however, are similar to those observed in human disorders characterized by hemolysis and thrombosis, such as thalassemia and sickle cell disease (Smith, 1996;Eldor and Rachmilewitz, 2002;Ezov et al, 2002;Shabat et al, 2004). Furthermore, enhanced red blood cell and endothelial cell interaction has been demonstrated both in this animal model and human thrombotic diseases Yedgar et al, 1999;Koshkaryev et al, 2003).…”
supporting
confidence: 76%
“…Splenectomised patients have higher plasma hemoglobin level than non-splenectomised thalassemia intermedia and higher circulating hemoglobin containing vesicles suggest that worsening of pulmonary hypertension after splenectomy may be due to increased cell free plasma haemoglobin [12]. Moreover, hyper coagulable state in thalassemia is already well established [12,14]. Pulmonary thromboembolism was also found in a large number of our splenectomised as well non-splenectomised patients with hemolytic anemia this has been demonstrated by other workers too [7,15].…”
Section: Discussionsupporting
confidence: 72%
“…Tripatara et al [20] demonstrated the existence of a low grade consumptive coagulopathy among transfused splenectomized patients with severe clinical manifestations, indicating that these patients may have a higher risk for thrombosis than comparable patients with intact spleen. Prothrombotic hemostatic anomalies, including low levels of coagulation inhibitors, such as protein C and protein S as well as thrombocytosis and platelet activation, have also been observed in these patients [21]. Cardiac ejection fractions and pulmonary artery pressures were measured by 2D transthoracic echocardiography and Doppler study.…”
Section: Discussionmentioning
confidence: 99%